Atypical Presentation of Advanced Diffuse Large B Cell Lymphoma of Germinal Center Subtype in a Young Woman: A Case Report - Wahinuddin Sulaiman; Amirul Muhaimin Ishak; Erra Edzaty Othman; Mahirah Munif; Mohd Irfan Danish Ibnu; Shafinaz Sabudin; Kamini Kirubamoorthy; Aruku Naidu (Asian Journal of Medicine & Health Sciences, 2022)
Diffuse large B-cell lymphoma (DLBCL) is the most common subtype and is known to be an aggressive type of non-Hodgkin lymphoma that develops from the B cells of the lymphatic system. DLBCL may occur at all ages but is more common in the elderly. Extranodal manifestation is common in non- Hodgkin lymphoma. DLBCL commonly incidentally diagnosed in patients of otherwise healthy or with atypical clinical manifestations. The prognosis of DLBCL is found to be better in young age patients. We report a young woman who presented with acute gastroenteritis symptoms, advanced stage of DLBCL diagnosed from incidental findings. She responded to R-CHOP chemotherapy regime followed by autologous hematopoietic stem cell transplantation (ASCT) and remained in remission for a year before she developed relapse and succumbed to the illness.